Feasibility of Implementing a Metadata Service for Cataloguing in Tamil - Ketheeswaren, S.; Charles, E.Y.; Chandrasekar, K. (Sri Lanka Library Association, 2023)
This study examined the feasibility of introducing a metadata service for cataloguing records in Tamil. The main objective was to determine the potential benefits and challenges associated with this, a survey methodology was employ feasibility of the metadata service. The results of the study indicate that a metadata service would be a valuable tool for cataloguing records in Tamil. However, the study also highlights technical difficulties, such as i connectivity issues, that may present significant challenges in implementing the service. The study also identifies the need for computer literacy programmes for librarians before implementing the metadata service. Furthermore, the study concludes that the introduction of a metadata service is unlikely to reduce cataloguing time or the need for human resources. study specifically offers valuable insights into the potential benefits and challenges that arise from the introduction of a metadata se libraries located in the Jaffna district.
Keywords: Metadata Service; Co-operative cataloguing; Bibliograpich control; Copy cataloguing